2018
DOI: 10.21660/2018.50.ijcst1
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Transcritical Co2 Refrigeration System for Supermarket Application

Abstract: Environmental issues becomes a priority on the refrigeration system development. The main issues are global warming and ozone depletion which are emitted from the conventional refrigeration system. One of the natural and clean refrigerants is Carbon dioxide (CO 2 ). CO 2 refrigeration system however still has low performance when operating at high ambient temperature. This study aim is to investigate the performance of CO 2 transcritical refrigeration system in high outdoor temperature. The research was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Compared to standard designs (without internal heat exchangers) that have been studied previously, the design consists of 14 state points [2,13] with sub cooled degrees in the saturated position (without sub-cooled). Previous studies also show that sub cooling degrees are very significant to improve the performance of CO2 refrigeration systems up to 30% [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to standard designs (without internal heat exchangers) that have been studied previously, the design consists of 14 state points [2,13] with sub cooled degrees in the saturated position (without sub-cooled). Previous studies also show that sub cooling degrees are very significant to improve the performance of CO2 refrigeration systems up to 30% [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…It is found that COP varies with ambient temperature and work pressure, the higher the external environment temperature, the lower the COP, so it is very clear that application to high temperature environments requires design modifications to increase the COP of the system [2]. Tsamos et al [3] examined several system configurations to be tested at ambient temperatures (warm climate).…”
Section: Introductionmentioning
confidence: 99%
“…With annual leak rates up-to 30%, HFC systems release greenhouse gases that deplete stratospheric ozone (Besher et al, 2015). CO 2 has a much lower GWP than HFC, so is the preferred refrigerant for retail in terms of net zero goals (Santosa et al, 2018;Dilshad et al, 2019;Efstratiadi et al, 2019;Yu et al, 2019). However, CO 2 -based systems are less efficient than HFC systems in hot climates (Fricke et al, 2019), implying a trade-off between the implications for net zero goals and climate mitigation, and for climate adaptation.…”
Section: Implications Of Adaptation Measures For Net Zeromentioning
confidence: 99%
“…Refrigeration system has developed both in term of component development and in term of being environmentally friendly, since the refrigeration system contribute to increased CO2 levels in atmosphere and can also damage the ozone which protects earth living from dangerous radiation of the sun shine [1,2]. However, natural refrigerant such as carbon dioxide (CO2-R744) is certainly excellent for the environment friendly but at present it still has several weaknesses, especially in term of high-pressure safety and efficiency of the system [3], so that investment and operation are still more expensive being compared with the conventional refrigerant such as, R134a, R600a.…”
Section: Introductionmentioning
confidence: 99%